Starburst : Color Photography in America 1970-1980 - Moore, Kevin; Crump, James; Rubinfien, Leo (Ostfildern : Hatje Cantz, 2010)
Heinecken, Robert ; Shore, Stephan ; Epstein, Mitch ; Levitt, Helen ; Meyerowitz, Joel ; Sonneman, Eve ; Slavin, Neal ; Krims, Les ; Sternfeld, Joel ; Christenberry, William ; Eggleston, William ; Groover, Jan ; Kasten, Barbara ; Divola, John ; Pfahl, John ; Misrach, Richard ; Callahan, Harry ; Rubinfien, Leo
boek